The Effect of Multiple Glass Beads Sterilization Cycles on Cyclic Fatigue of AF Blue S One File - Bassam Alsheekhly1 , Marwah M. Adnan2 , Fudhla Sadoon Al- Zubaydi3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Sterilization represent an important and essential aspect, now days Most of the dentists usually use the endodontic files for many times before they discard it, this could increase the need for reliable and fast sterilization method, but without affecting the physical properties of the endodontic files. Aim of the Study: This study discusses an economic method of sterilization (glass bead) and its effect on the fracture resistance of the AF Blue S one file (Fanta) with multiple reuses of the system. Method and Materials: A total of 75 AF BLUE S one NiTi Rotary files (FANTA) #25 size with 0.04 taper and 25 millimeter length, were used in this study, divided into three groups to test their cyclic fatigue resistance after multiple sterilization cycles. Result: The results were statically analyzed using (SPSS) software, Anova test showed a statically high significant differences between the groups. Conclusions: Within the limitation of this study, it can be concluded that AF Blue S one file with 4 time glass bead sterilization cycle was the most fatigue resistant compared to zero and two sterilization cycle.